Representation of Islamic Women in the Novel Khadijah: Ketika Rahasia Mim Tersingkap and Lesson Plan - Fitri Septi Triani; Khalidatun Nuzula (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze: 1) the representation of Islamic women in the novel Khadijah: Ketika Rahasia Mim Tersingkap by Sibel Eraslan through the perspective of Islamic feminism by K.H. Husein Muhammad, with a focus on the public sphere; 2) the lesson plan for the representation of Islamic women in the novel Khadijah: When Mim's Secret is Revealed. The study uses a qualitative approach with a document analysis method. The tool used to collect research data is an observation guide sheet. Text quotation data in the novel that represent the role and position of the character Khadijah as a Muslim woman are analyzed descriptively. The analytical framework is based on the concept of Islamic feminism by K.H. Husein Muhammad, including women's jihad, monotheism as the basis of justice and gender equality, women's participation in the public and political spheres, and the role of women in building the future of civilization. The results of the study show that: 1) the character Khadijah is represented as an independent, empowered, and active woman in social, economic, and spiritual life. Khadijah is not placed solely in the domestic sphere, but is shown as the main subject in moral struggle, strengthening da'wah, economic management, and generation education. This representation is in line with the Islamic feminist thoughts of K.H. Husein Muhammad who emphasized women as equal subjects in social structure; 2) the learning plan for the representation of Islamic women in the novel Khadijah: When Mim's Secret is Revealed involves an innovative strategy using manual teaching materials for grade XI high school students involving 3 initial activities, 17 core activities, and 2 final activities.